The percentage of the contribution of emotional achievement in the results of cognitive and skill learning to the skills of passing from the top and bottom of volleyball - Shaimaa Adil; Dr. Nuhad Mohammed (الرياضة المعاصرة, 2021)
The study aimed to identify the relationship between the emotionality of achievement with the results of cognitive and skill learning of the two preparation skills from the top and the bottom in volleyball, and to identify the percentage of the contribution of the emotional achievement in the two outcomes of cognitive and skill learning to the two skills of numbers from the top and bottom in volleyball. Corresponding to the nature of the research problem, while the research community and sample are represented by the second stage students of the Department of Physical Education and Sports Sciences, Faculty of Knowledge - Anbar University for the academic year (2020-2021) and their number (69) students. The research samples were chosen randomly. The study found that the emotionality of learning acquisition has a positive role in the cognitive and skill learning outcomes for the performance of the two numerical skills from the top and from the bottom. For the learner and raising their positive emotions during the learning units because of their positive role in mastering the performance of skills, and conducting studies similar to the current study other mathematical skills